Microcontroller based water tank management monitoring system / Siti Aishah Che Kar ... [et al.] - Che Kar, Siti Aishah; Md Enzai, Nur Idawati; Mohd Hatim, Ahmad Faidhi; Mohd Amidon, Aqib Fawwaz; Mohd Sapawi, Ahmad Faris Firdaus (2017)
The water quality and quantity monitoring system is designed to give an early warning detection of home water tank. The design of this project is based on ATmega328P microcontroller as the main controller for the whole system. The ultrasonic sensor and pH probe are used as inputs to the system. All the signal inputs from Ultrasonic sensor and pH probe will be transmitted to the microcontroller. The microcontroller will process the inputs and determine the consequence outputs. The 16 x 2 character LCD display, buzzer and the LEDs are used as outputs. The LCD will display the remaining water level in the tank and water quality continuously. The three LEDs are used as indicator in this project to indicate three stages of water level which are: high level, medium level or low level. Lastly, a buzzer is used as an alarm and will be activated when the water level is at the lowest level. Basically, this system is designed to aid home owners in monitoring supply and safety of water tap in their home.